Analysis of optimization waste transportation using saving matrix and floyd warshall methods in Binjai - Sari, Dinda Permata; Sari, Rina Filia (Desimal: Jurnal Matematika, 2024)
Waste is defined as anything that is not utilized or discarded. Waste is not something that happens by itself; instead, it is a product of human activity. Unresolved problems are often caused by waste. Binjai City's waste problem is one example. In Binjai City, waste transportation is done once a day. The capacity of the truck is only 6–8 m3 or 3-5 tons, so if it is full, the waste is immediately transported to the landfill. Then the collection of waste at each TPS is not possible. Optimization of waste transportation routes using Floyd Warshall and Saving Matrix techniques is one way to overcome this problem. When scheduling cars, the Savings Matrix approach can be used to combine multiple delivery points and take into account the maximum capacity of the vehicle. The Floyd Warshall method is a dynamic programming component that is well suited to solving route optimization problems and can find every potential path between any two locations. Based on an analytical procedure that includes the Floyd Warshall algorithm and the Saving Matrix. These two routes of 29.46 kilometers were first used by the Environmental Agency of Binjai City. 20.63 km is the overall distance when using Saving Matrix, and 23.55 km is the overall distance when using Floyd Warshall. This shows that the Saving Matrix approach is more successful in reducing travel costs and distance.